Technologically Driven Approaches for the Integrative Use of Wild Blackthorn (Prunus spinosa L.) Fruits in Foods and Nutraceuticals - Oana Viorela Nistor; Ștefania Adelina Milea; Bogdan Păcularu-Burada; Doina Georgeta Andronoiu; Gabriela Râpeanu; Nicoleta Stănciuc (MDPI AG, 2023)
Different technological approaches were used in this study for the valorization of blackthorn (Prunus spinosa L.) fruits in marmalade, jam, jelly, and nutraceuticals. Marmalade showed the highest concentrations of polyphenols (7.61 ± 0.05 mg gallic acid equivalents/g dry weight (DW)) and flavonoids (4.93 ± 0.22 mg catechin equivalents/g DW), whereas jam retained the highest content of anthocyanins (66.87 ± 1.18 mg cyanidin-3-O-glucoside equivalents/g DW). A good correlation between polyphenol and flavonoid contents and antioxidant activity was found, the highest value being 21.29 ± 1.36 mmol Trolox/g DW for marmalade. Alternatively, the fresh pulp was enriched with inulin, followed by inoculation with Lactobacillus acidophilus, and freeze-dried, allowing a powder to be obtained with a viable cell content of 6.27 × 107 CFU/g DW. A chromatographic analysis of blackthorn skin revealed that myricetin (2.04 ± 0.04 mg/g DW) was the main flavonoid, followed by (+)-catechin (1.80 ± 0.08 mg/g DW), (−)-epicatechin (0.96 ± 0.02 mg/g DW), and vanillic acid (0.94 ± 0.09 mg/g DW). The representative anthocyanins were cyanidin 3-O-glucoside, cyanidin 3-O-rutinoside, and peonidin 3-O-glucoside, with an average concentration of 0.75 mg/g DW. The skin extract showed comparable IC50 values for tyrosinase (1.72 ± 0.12 mg/mL), α-amylase (1.17 ± 0.13 mg/mL), and α-glucosidase (1.25 ± 0.26 mg/mL). The possible use of kernels as calorific agents was demonstrated through the evaluation of calorific power of 4.9 kWh/kg.